Tunable Halide Perovskites for Miniaturized Solid‐State Laser Applications. Issue 17 (25th March 2019) - Liao, Qing; Jin, Xue; Fu, Hongbing
Abstract: Halide perovskites have shown great potential in optoelectronic applications, such as a record photovoltaic efficiency of 23.3%, and an achievement of external quantum efficiency beyond 20% in perovskite light‐emitting diodes, as well as other promising demonstrations of light‐emitting transistors and photodetectors. Moreover, the extraordinary optoelectronic properties of optical absorption, high photoluminescence quantum yield, low non‐radiative recombination rates, large and balanced charge‐carrier mobilities, and high gain coefficients extend their applications into the coherent light sources (laser) field. However, although halide perovskites have made great progress, the realization of solid‐state electrically pumped lasers has not been achieved yet. This review starts with a discussion of the structure, optical properties, and gain behaviors of various perovskite materials. Then, the rapid advances of perovskite‐based laser applications are reviewed, in which they are mainly classified into three sections: optically pumping lasers, strong‐coupling lasers, and continuous‐wave pumped lasers. Finally, the conclusions and some remaining challenges for perovskite electrically driven lasers are highlighted. Abstract : Halide perovskites have shown great potential in the coherent light sources (laser) field due to their extraordinary optoelectronic properties. Current advances in miniaturized lasers of metal halide perovskites are highlighted. The fundamental structure, optical properties, gain behaviors, and laser applications based on halide perovskite are discussed toward electrically driven lasers.